A critical review on analytical methods and characterization of butyl and bromobutyl rubber. Issue 4 (19th May 2017) - Vitiello, R.; Tesser, R.; Turco, R.; Santacesaria, E.; Compagnone, G.; Di Serio, M.
ABSTRACT: The molecular structure characterization of butyl and bromobutyl rubber (BIIR) requires the definition of three main parameters: (I) the unsaturation degree of the rubbers, (II) the total bromine content of the BIIRs, and (III) the functional bromine content of the BIIRs. The analytical methods for the determination of the previously mentioned parameters have been described and critically examined in this review.